Clinical Assessment of Mitral Valvular Diseases Requiring Its Prosthetic Replacement - Mrinmoy Talukdar; Probin Ch Gogoi; Ranjumoni Konwar (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objectives: The patient’s clinical assessment having mitral valvular diseases requiring its prostheticreplacement was done in the current study. Methods: The study included 45 selected cases of the mitralvalvular lesion that underwent prosthetic replacement of mitral valve admitted in the cardiothoracic surgerydepartment at a tertiary care centre. A detailed history of each patient was taken, and subsequent managementand follow up was done. The pre-operative clinical features of the patients were presented in terms offrequencies. Results: The patient’s peak age group was 31 to 40 years, comprising 42.22%. There was a femalepredominance with 28 (62.22%) patients. Dyspnea was the presenting feature in all 45 (100%) patients.Valvular lesions of the patients were diagnosed with Mitral stenosis, Mitral regurgitation and combinedvalvular lesion. In the present study, valvular lesions were predominantly associated with Rheumatic fever’shistory in 24 (53.33%) patients. Calcification was noted either in valve leaflet or annulus in 12 (26.66%)cases. Calcification was confirmed by pre-operative echocardiography and during the perioperative period.It is equally noted in mitral stenosis cases and combined valvular lesion. The maximum 33 (73.33%) patientsbelonged to the NYHA Class III, followed by Class IV. The associated other valvular lesions mainly were in7 (15.55%) cases that belonged to mild aortic regurgitation. 36 (80%) cases were diagnosed with left atrialenlargement followed by right ventricular enlargement for 23 (51,11%) patients. Left atrial hypertrophywas the most common feature for 39 (86.66%) cases. Conclusion: During the pre-operative period, clinicalassessment is critical to determine the extent of illness and type of valvular diseases. The results of this studyare comparable to other similar published clinical observations.